A práxis pedagógica de professores que ensinam matemática em salas de recursos multifuncionais nos anos iniciais - Silva, Alessandra Aparecida dos Reis (2022)
The Brazilian legislation guarantees the access of all students to the school space, with or without disabilities, and in this case, Special Education is necessary in order to achieve quality learning, with the construction of an Inclusive Education being a challenge. In this process, it is very important to verify the attendance to students with Special Educational Needs enrolled and assisted by Special Education, through the Multifunctional Resource Rooms. Thus, this research presents the perception of teachers work at Multifunctional Resource Rooms and their pedagogical praxis in Mathematics. Thus, this study had as main objective to identify the pedagogical praxis of teachers who teach Mathematics in the Multifunctional Resource Rooms of the Early Years of Elementary School in the municipality of Foz do Iguaçu/PR. Its specific objectives sought to: characterize the professionals in these workspaces; characterize the professionals in these workspaces; to know the professionals’ perceptions about how to perform the teaching action in the Multifunctional Resource Rooms; identify the difficulties of these teachers in relation to pedagogical practice in Mathematics; report the factors that hinder the learning of Mathematics and; Highlight the characteristics needed by teachers who work in the Multifunctional Resource Rooms. And to see how the Specialized Educational Service happens in this environment with students with disabilities, pervasive developmental disorders, specific functional disorders and high abilities/giftedness is very important, since the teaching of Mathematics needs referrals directed to the students who have specificities. Given this scenario, the research, which is qualitative, took on an exploratory character, and data collection took place through a questionnaire sent to the teachers of the Multifunctional Resource Rooms of the Municipal Education Network of Foz do Iguaçu/PR and, divided into three blocks, dealt with the identification of teachers; the conception of the teachers regarding the Multifunctional Resource Rooms and; their pedagogical praxis in Mathematics. For data analysis, an appreciation inspired by Discursive Textual Analysis was chosen. The research proves to be relevant, because the Specialized Educational Assistance carried out in the Multifunctional Resource Rooms is still a new issue in the school universe with regard to its work forwarding and, therefore, this information and reflections on the subject allow the improvement of the quality of Mathematics teaching in these classrooms, in addition to being able to direct referrals to more assertive and punctual continuing education on the topics suggested here. In view of the results, it was found that students with Special Educational Needs are being assisted through the Multifunctional Resource Rooms; that teachers, for the most part, meet what is recommended in official documents regarding training; the understanding of pedagogical praxis in Mathematics can be considered acceptable, as they understand what praxis is, they have knowledge about their area of expertise and their conception of Multifunctional Resource Rooms is clear. In this sense, it is considered important to continue seeking improvements in the quality of the pedagogical practices of teachers in the Municipal Network, since Inclusive Education is already a reality in the municipality, and collaborative work is of paramount importance for its effectiveness, although this is still incipient; and in the curricular component of athematics,insecurity needs to be mediated with continuing education, enhancing teaching action permeated by reflection, effecting critical and transforming thinking in all those involved.